Portrait of literary works by Riau Authors using a knowledge graph - Yusrianda, Tiara; Sudiar, Nining; Monika, Winda; Nasution, Arbi Haza (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. The literary works produced by Riau authors are generally documented in unstructured text formats, making it difficult to organize, search, and access information efficiently. This study aims to visualize literary works through the implementation of a knowledge graph to provide more structured and integrated access to literary information. Data Collection Methods. This research adopts a Research and Development (R&D) approach involving five stages: needs analysis, design, development, testing, and evaluation. Metadata was systematically collected based on the standards of Resource Description and Access (RDA) and Friend of a Friend (FOAF) to ensure consistency and interoperability of information. Data Analysis. The collected metadata was analyzed and used to represent the relationships between authors and their literary works within a semantic framework using Neo4j. Results and Discussion. This study successfully compiled and structured the metadata of literary works by Riau authors and clearly mapped the relationships between entities in an informative manner. Conclusion. The application of knowledge graph technology in the context of regional literature has proven effective in enhancing the organization, visualization, and accessibility of literary metadata. This research contributes to the digital preservation of local literary heritage and offers an information management model that can be further developed.